Everyone included : improve belonging, diversity and inclusion in your team - May, Helen (Leadership consultant) (Pearson, 2021)
"In the increasingly divided, volatile and often perplexing world we are living in today, organisations are realising that, in order to protect the well-being and maximise the potential of their number one asset, their people, traditional approaches to diversity and inclusion (D&I) need a rethink. This book shows how shifting the focus to building a culture of belonging is the solution that will transform organisations, improve the lives of employees and create agile environments fit to adapt to challenges organisations are facing today and in an unpredictable future"--